Does Participation in a Pain Course Based on the International Association for the Study of Pain’s Curricula Guidelines Change Student Knowledge about Pain? - Jenny Strong; Pamela Meredith; Ross Darnell; Marlene Chong; Patricia Roche (Pain Research and Management)
BACKGROUND: The People in Pain course was set up as a joint initiative of the Departments of Occupational Therapy and Physiotherapy within the School of Health and Rehabilitation Sciences at The University of Queensland. It was instigated in response to the publication of Pain Curricula for Occupational Therapy and Physiotherapy by the International Association for the Study of Pain (IASP) in 1994 (1). The first year it was offered, the 'People in Pain' course comprised 14 h of lecture content. It was then expanded to encompass 28 h of lectures and seminar involvement.